Web-Quest as a Means of Developing Flexible Skills of Future Lecturers in a Higher Educational Institution - N. N. Kolosova (Открытое образование (Москва), 2024)
The purpose of the study is a scientific justification and experimental verification of the effectiveness of using web-quest technology in the process of forming flexible skills of future lecturers in a higher educational institution.Rapid socio-economic development, informatization of all spheres of human activity determine the need for appropriate changes in the education system. Today, a modern lecturer requires not only basic psychological and pedagogical knowledge and skills, but also communication skills, responsibility, the ability to work in a team, resolve conflicts, and think critically and other flexible skills responsible for efficiency and high productivity, contributing to professional development and self-realization. In this regard, education in higher educational institutions should focus not only on the development of professional special skills (hard skills), but also on the formation of flexible skills (soft skills), since they are universal, updated over time and become increasingly important in the professional activity of a lecturer. There are quite a lot of technologies that contribute to the formation of flexible skills of students, one of which is the innovative technology of the web-quest, which, thanks to its unique form, content, teaching and control methods, structured information content, seems to be as effective as possible. Thus, the problem of purposeful formation of flexible skills among future lecturers, the search for the necessary mechanisms and resources for this, and the study of the potential of the web-quest determine the relevance of the research.Materials and methods: in the course of the study, methods of studying and analyzing psychological, pedagogical and methodological literature were used, summarizing the experience of using web-quests in the educational process of the university. The methodological basis of the study was a set of approaches: personality-oriented, systemic, activity-based, competence-based, interdisciplinary and reflective. Results: the author’s definitions of the concepts “flexible skills of future lecturer” and “web-quest” are presented, the flexible skills of a modern lecturer are characterized, the specifics, structure and methodology of conducting a web-quest, its impact on the purposeful formation of flexible skills are described in detail, an example of a web-quest “The essence of professional competence of a lecturer”, developed and tested in the work with students, is given of the training area 44.03.01 Pedagogical education.The practical significance of the research lies in the fact that its results, as well as the content and information resources of the proposed web-quest, can be used in the practice of higher pedagogical education.